Supportive Home Remedies for Orofacial Pain during the Coronavirus Disease 2019 Pandemic: Their Value and Limitations - Yeon-Hee Lee (Hindawi Limited, 2022)
Background. The coronavirus disease 2019 (COVID-19) pandemic has impeded access to timely dental care, and there is an urgent need for adjuvant therapies that can reduce orofacial pain in emergencies. Aims. To provide information on the benefits and limitations of eight representative home remedies as palliative care for orofacial pain during the coronavirus disease 2019 (COVID-19) pandemic. Methods. PubMed and Medline were electronically searched for eight home remedies for orofacial pain that can be used in COVID-19. Papers published in English in the past 30 years were considered. Among the published studies suitable for the research purpose, those in which the abstract and body text were confirmed were targeted, and duplicate studies were excluded. Finally, 86 studies were included. Results. There is extensive and high-level scientific evidence for the application of tooth brushing and flossing, mouth rinsing with chlorhexidine, use of over-the-counter pain medication, and application of cryotherapy in emergencies. Gargling with salt water, brushing with bamboo salt, gargling with garlic juice, and oil pulling are traditional methods used for centuries. The use of natural products for orofacial pain has a significant empirical effect but has weak scientific evidence. Conclusions. Knowing the correct application method, effects, and side effects is desirable to use these methods appropriately in emergencies. However, scientific evidence is unclear and generally lacking for home remedies to be the main treatment strategy, and there are clear limitations to their use as a single main treatment.